The school after the emergency: perspectives and reflections on didactics starting from the national SIRD survey - Lucisano, Pietro; Stanzione, Irene; Morini, Arianna L. (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2021)
Following the first wave of the pandemic, which forced schools of all levels to implement Distance Learning, with the resumption of the new school year (2020/2021) we moved to the now well-known “Integrated Digital Didactics” (DDI). With this in mind, it is essential that educational research be oriented to identify with scientific methodology the aspects that have characterized Distance Learning in order to help define innovative teaching strategies and policies to be implemented during and after the emergency period. With these intentions, the Italian Society of Educational Research (SIRD) conducted a national study entitled “A comparison of distance learning methods adopted in Italian schools during the COVID-19 emergency period”. The study involved the completion of a questionnaire constructed upon ten thematic areas, intended for teachers throughout the country and to which more than 16,000 responded. The educational challenges do not end with the immediate crisis. With this paper, starting from a cross-sectional analysis of quantitative and qualitative data conducted on the Lazio unit of analysis, we aim to identify those aspects that could, potentially, become elements of quality in our school system in the future.